2018
DOI: 10.1002/macp.201800295
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Foaming Kinetics in Epoxidized Natural Rubber Foams Crosslinked by Electron Beam Irradiation

Abstract: This work focuses on studying natural rubber (NR) and epoxidized natural rubber (ENR) foams crosslinked at different absorbed doses and foamed using a chemical blowing agent. The aim is to study if the existence of epoxide groups within the natural rubber molecular structure influences the expansion capacity and the cellular structure morphology of these types of foam. This is accomplished by studying the foaming kinetics, that is, by quantifying the evolution of density and cellular structure parameters, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…It was interpreted that the formation of the epoxy groups increased the rigidity of the macromolecular chain. This finding is consistent with that of the previous studies ,, about the effect of epoxidation on the glass transition temperature. Moreover, after DOPO grafting onto the macromolecular chain, T g increased more significantly.…”
Section: Resultssupporting
confidence: 94%
“…It was interpreted that the formation of the epoxy groups increased the rigidity of the macromolecular chain. This finding is consistent with that of the previous studies ,, about the effect of epoxidation on the glass transition temperature. Moreover, after DOPO grafting onto the macromolecular chain, T g increased more significantly.…”
Section: Resultssupporting
confidence: 94%
“…This improvement was attributed to the ring-opening reaction between the epoxy groups of ENR and the Si-OH groups on the silica surface which improved the dispersion of silica in the rubber matrix and enhanced the interfacial interactions between rubber and silica ( Figure 4 ). Salmazo et al produced SMR-L and ENR-25 foams separately in the presence of ADC and cured with different electron beam irradiation doses (50, 100 and 150 kGy) [ 108 ]. Their results revealed that ENR foams had higher cell nucleation rates and less cell degradation than those produced from SMR-L alone.…”
Section: Rubber Foaming Formulationmentioning
confidence: 99%
“…Density and indentation hardness are important physical parameters for NRLFs because density dictates the weight of the final products for lightweight design applications. Additionally, indentation hardness impacts the load-bearing capacity of the foam, especially for body-supporting applications [11] , [37] . Fig.…”
Section: Resultsmentioning
confidence: 99%